Transformative Perspectives in Education: Highlights from CJNSE and CCGSE Collaboration - Cameron Smith; Amanda Battistuzzi; Aide Chen; Nathan Rickey (Canadian Society for Studies in Education, 2023)
For the second consecutive year, The Canadian Journal for New Scholars in Education (CJNSE) and the Canadian Committee of Graduate Students in Education (CCGSE) have united to bring forth a Special Issue that showcases the innovative work of Canada's graduate students in education. Stemming from some of the enlightening presentations at the 2023 CCGSE/CSSE conference, this issue aims to amplify the voices of emerging scholars, providing them with a platform where their research undergoes a rigorous peer-review process and reaches a wider academic audience.